Benefit assessment of EDOTCO Bangladesh's solar capex investment and sustomer satisfaction - Sajid, Rohan Zaman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of masters of Business Administration, 2023.